Political Economy - May, Christian. author. (orcid)0000-0001-7550-8747 Link aut Link
XVII, 303 p. 48 illus.
Keywords: This textbook offers a comprehensive introduction to Political Economy. It combines comparative, international and historical perspectives into a holistic framework of analysis. Drawing on the work of Karl Polanyi, the book shows how capitalist economies differ around the globe and how they are embedded in the international economic order. Through a critical-institutionalist lens, it helps to account for the evolution of contemporary capitalism and addresses current topics at the intersection of political science and economics. Students and instructors can draw on supplementary material, such as Power Point slides with all figures and tables as well as the Springer Nature Flashcards app with exercises. The Authors Dr. Christian May is Research Associate at Goethe University Frankfurt, Germany, Dr. Daniel Mertens is Professor of International Political Economy at the University of Osnabrück, Germany. Dr. Andreas Nölke is Professor of Political Science, in particular International Relations and International Political Economy, at Goethe University Frankfurt, Germany. Dr. Michael Schedelik is Research Associate at Goethe University Frankfurt, Germany. .